A study on the incidence and maternal/neonatal characteristics for fetal and neonatal alloimmune thrombocytopenia at Malaysia National Blood Centre - Nalliappan, Parameswari; Appannah, Geeta; Noordin, Siti Salmah; Ahmad, Nor Hafizah; Mohamad, Siti Mardhiana (Universiti Putra Malaysia, 2021)
Introduction: Fetal and neonatal alloimmune thrombocytopenia (FNAIT) is an uncommon condition due to maternal alloimmunization of fetal platelet leading to thrombocytopenia in fetal and neonate. Our study determine the incidence, common platelet alloantibodies and the associated maternal and neonatal factors of FNAIT in Malaysia. Methods: Matched case control study of FNAIT and control (39 FNAIT cases and 39 randomly selected controls) through retrospective record review from the year 2011 to 2019 was performed at National Blood Centre, Malaysia. Data were analysed using Statistical Package for Social Sciences (SPSS) version 26.0. Differences between cases and controls were evaluated using chi-square test for categorical variables and t-test or Mann-Whitney test for normally and non-normally distributed variables. Results: The incidence of FNAIT in Malaysia was 0.85 per 100 000 live births. Common anti-Human Platelet Antigen (-HPA) identified in this study were Anti-HPA-5b, Anti-HPA-3a and Anti-HPA-5a. Fifty-eight (58%) (p=0.012) of mothers in the study were younger than 35 years old, of Malay ethnicity and multiparous. Malay mothers were five times more likely to develop FNAIT as compared to non-Malay. For neonates, the most significant factor associated with FNAIT was the neonatal presentation. Symptomatic neonates were more likely to develop FNAIT. Whereas, the neonates onset of presentation, platelet count and blood group were not significantly different than in control group. Conclusion: Incidence of FNAIT among Malaysians was lower than reported in the literature. Malay mothers and neonates presenting with symptoms are more likely to have FNAIT,